Sistem Informasi Pencarian Jasa Tukang Berbasis Android (Studi Kasus: Bandar Lampung) - Muhammad Arsi; Qadhli Jafar Adrian; Dyah Ayu Megawaty (Universitas Teknokrat Indonesia, 2023)
Science and technology continues to develop rapidly, this development is not only in a matter of years, months or days but hours, minutes and even seconds, especially related to information and communication technology which is supported by electronic technology. This condition causes an increase in the need for information through gadgets. One of them is to look for handyman services online through an application on a smartphone. To get a handyman's needs that suit the user, they are usually faced with the problem of prices that are not in accordance with the users budget and user dissatisfaction with the results provided by the handyman because they are just haphazardly looking for a handyman to do home repairs. The Android-based handyman search application is an application that can be used as a medium to help the public in ordering or searching for handyman services, getting trusted and quality handymen according to their field on the handyman side, which can also be used for media promotion and is more effective for increasing income.